Time- and angle-resolved photoemission spectroscopy of solids in the extreme ultraviolet at 500 kHz repetition rate - Puppin, M.; Deng, Y.; Nicholson, C. W.; Feldl, J.; Schröter, N. B. M.; Vita, H.; Kirchmann, P. S.; Monney, C.; Rettig, L.; Wolf, M.; Ernstorfer, R. (Review of scientific instruments, 2019)
Time- and angle-resolved photoemission spectroscopy (trARPES) employing a 500 kHz extreme-ultraviolet light source operating at 21.7 eV probe photon energy is reported. Based on a high-power ytterbium laser, optical parametric chirped pulse amplification, and ultraviolet-driven high-harmonic generation, the light source produces an isolated high-harmonic with 110 meV bandwidth and a flux of more than 1011 photons/s on the sample. Combined with a state-of-the-art ARPES chamber, this table-top experiment allows high-repetition rate pump-probe experiments of electron dynamics in occupied and normally unoccupied (excited) states in the entire Brillouin zone and with a temporal system response function below 40 fs.